Revealing Developers’ Arguments on Validating the Incidence of Code Smells: A Focus Group Experience - Junionello, Luis Felipi; de Mello, Rafael; Oliveira, Roberto; Sousa, Leonardo; López, Alexander; Garcia, Alessandro (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2021: Anais do IX Workshop de Visualização, Evolução e Manutenção de Software, 2021)
Identifying code smells is considered a subjective task. Unfortunately, current automated detection tools cannot deal with such subjectivity, requiring human validation. Developers tend to follow different, albeit complementary, strategies when validating the identified smells. Intending to find out developers' arguments when validating the incidence of code smells, we conducted a focus group session with developers familiar with identifying code smells. We distributed them among two groups, in which they had to argue about the incidence of a code smell: either accepting or rejecting its presence. Based on their arguments, we compiled a set of general heuristics that developers follow when validating smells. We then used these heuristics for composing validation items. We understand that the set of validation items proposed may support developers in reflecting on the incidence of code smells. However, further studies are needed for reaching a more comprehensive and optimized set. The experience of this study reveals that conducting focus group sessions is helpful to emerge the tacit knowledge of developers when validating code smells.